2018
DOI: 10.1002/humu.23565
|View full text |Cite
|
Sign up to set email alerts
|

Results of next-generation sequencing gene panel diagnostics including copy-number variation analysis in 810 patients suspected of heritable thoracic aortic disorders

Abstract: Simultaneous analysis of multiple genes using next‐generation sequencing (NGS) technology has become widely available. Copy‐number variations (CNVs) in disease‐associated genes have emerged as a cause for several hereditary disorders. CNVs are, however, not routinely detected using NGS analysis. The aim of this study was to assess the diagnostic yield and the prevalence of CNVs using our panel of Hereditary Thoracic Aortic Disease (H‐TAD)‐associated genes. Eight hundred ten patients suspected of H‐TAD were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 76 publications
1
30
0
Order By: Relevance
“…For example, approximately 8% of reported results from GeneDx exomes (over 100,000 exome have been run in total, including currently >1,500 cases/month) are CNVs. Studies of cohorts affected by other conditions have identified significant rates of causative CNVs by next‐generation sequencing (NGS; Bergant et al, ; Overwater et al, ; Tsuchida et al, ). The detection of other structural variants as well as mosaicism by NGS, including from exome, genome, and targeted panels, is also improving (Stosser et al, ).…”
Section: Further Causes and Future Investigationsmentioning
confidence: 99%
“…For example, approximately 8% of reported results from GeneDx exomes (over 100,000 exome have been run in total, including currently >1,500 cases/month) are CNVs. Studies of cohorts affected by other conditions have identified significant rates of causative CNVs by next‐generation sequencing (NGS; Bergant et al, ; Overwater et al, ; Tsuchida et al, ). The detection of other structural variants as well as mosaicism by NGS, including from exome, genome, and targeted panels, is also improving (Stosser et al, ).…”
Section: Further Causes and Future Investigationsmentioning
confidence: 99%
“…No more than 50 patients carrying disease‐causing TGFB3 variants have been reported so far . Here, we described genetic and clinical data from 32 TGFB3 patients from 17 families including the first homozygous individual.…”
Section: Resultsmentioning
confidence: 99%
“…Given the rarity of the disorder, with no more than 50 cases described so far, a precise delineation of its phenotype is yet to be determined …”
Section: Introductionmentioning
confidence: 99%
“…Cusp plication techniques may involve wedge resection of the calcified raphe, primary cusp plication over the nodule of Arantius, 29 or oversewing of the free cusp edge and commissural plication (Cabrol sutures). 27,28,30,31 Pericardial patch repair of the valve is no longer recommended owing to poor durability and increased risk of valve failure. 24,27 Risk factors associated with recurring AI after BAV repair include commissural orientation <160˚, Siever's type 2 BAV, and preoperative aortic valve annular diameter >29 mm.…”
Section: Aortic Valve Repairmentioning
confidence: 99%
“…54 Pertaining to the "genetic theory" the earliest, and perhaps most important gene is NOTCH, 55 as mutations are known to cause BAV and other cardiovascular defects such as aneurysms. 31,55 Pluripotent stem cells with a NOTCH1 mutation show impaired differentiation into smooth muscle cells and endothelial cells. 56 Currently, in humans there are approximately 10 other genes that are known to contribute to isolated and syndromic BAV.…”
Section: Bav Aortopathymentioning
confidence: 99%